Organizational culture as a risk factor in projects - Piwowar-Sulej, Katarzyna (Contemporary organisation and management. Challenges and trends, 2020)
The purpose of the article is to present organizational culture as a project risk factor. The author addressed the literature approach to risk areas in projects. It was highlighted that since every organization has its own culture, a single project as a micro-organization has its own too. There is feedback between these cultures. Finally, the research results on the impact of culture on project success were presented. The article is of theoretical and pragmatic nature. The conducted literature review shows some implications for both management practitioners and theorists. The literature review also identifies features worth implementing in an organizational culture. While there is a general agreement that, e.g., culture promoting cooperation has a positive impact on project success, it is not possible to explicitly answer the question which type of culture (taking into account different typologies) remains the best (some of the above was changed in the main article).